MONITORING OF THE PUBLIC DEBT OF UKRAINE UNDER THE CONDITIONS OF MARITAL STATE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. Public debt exists as an economic and legal phenomenon in most countries of the world, as a rule, it is formed as a result of financing the deficit of the national budget. For countries with effective public debt management institutions, it is an engine of rapid economic development. In many countries, the creation of public debt is associated with the government's attempts to improve the socio-economic conditions of people's lives by modernizing infrastructure, developing education, science, health care, improving social welfare, etc.Public borrowing is a source of investment, a means of reducing the negative impact of external factors, and a fairly effective incentive that helps accelerate the growth of the country's economic potential.Thanks to borrowing, our country received additional resources to meet public needs, overcome а certain technological lag in national development, and outline prospects for economic growth. But on the other hand, such borrowings can become a debt burden, since the economic situation in the country does not allow for effective repayment of debts, which in turn only deepens the country's debt problem. Thus, the main problem of public borrowing, in our opinion, is a real threat of reliance on the state and creditors, which has a stable upward trend.In the conditions of war, national obligations, mainly to foreign countries, are growing rapidly. Inefficient management of public debt can lead to economic instability in countries. In our opinion, an increase in external public debt can lead to a decrease in the state authority of Ukraine in the international economic arena and cause mistrust and doubts about the state's ability to ensure the timely fulfillment of its financial obligations.
Keywords: public debt, monitoring, public budget, deficit, debt policy